Comparison of watershed boundaries delineation for Kuantan River Basin - Adilah Nurain, Ahmad (2017)
Watershed also known as river basin is a part that covered every piece of land on the Earth because of water always moves off land to downstream point where it collects in a water body. Additionally, watershed modelling is an important step in preparation of data for modelling. This study is to delineate watershed boundaries using 3 different Digital Elevation Models (DEMs) and evaluate the accuracy of watershed boundaries derived from 3 difference sources for Kuantan River Basin. The software that was used to delineate watershed boundaries is Geographical Information System (GIS), ArcGIS version 10.2. The data was derived from 3 different DEMs, Shuttle Radar Topography Mission (SRTM) which consist two resolutions that is 1 arc-second (30-m) resolution and 3 arc-second (90-m) resolution and Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) with (30-m) resolution. Next the analysis is done by using Euclidean Distance in ArcGIS to obtain the differences in distance between DEMs boundaries and manual boundaries (DID). The result will be compared with the Kuantan River Basin that retrieved from Department of Irrigation and Drainage (DID). From the analysis, SRTM-30 m data have several advantages such as provide important fundamental data for topographic analysis in many fields. Not only that, it has the highest resolution topographic dataset ever produced for the Earth’s land surface. As for SRTM-90 m, it has a slight different from SRTM-30 m due to the different in resolution. Meanwhile, ASTER data has higher spatial resolution and wider coverage than the SRTM-30 m but have negative bias toward flat region. Thus, the accuracy of watershed boundaries derived from 3 different sources depends on the accuracy of the Digital Elevation Model (DEM) will be discuss in this paper.